Investigation of Na2SO4 Deposit Induced Corrosion of Cr, Al, C Binary and Ternary Thin Film Coatings on Ni-201. Issue 6 (15th March 2017) - Aw, Lik Ming; Amendola, Roberta; Ryter, John W.; McCleary, Madisen W.; Gannon, Paul E.; Leonard, McLain E.; Smialek, James L.
Abstract : Al-C, Cr-C, Al-Cr and Al-Cr-C thin film coatings were sputtered onto Ni-201 substrates. Samples were deposited with 1.0 ± 0.3 mg cm −2 Na2 SO4 and exposed to dry air/2 ppm SO2 gas atmosphere, at 700°C for 250 hours. Coated samples had reduced corrosion rates relative to uncoated samples. Al–C and Cr–C coatings were not effective since NiO was the only compound detected on the surfaces; in contrast Cr–Al and Cr–Al–C developed protective layers of Al2 O3 and Cr2 O3 with Cr–Al–C coated samples having the least corrosion rate.